From belonging to belief : modern secularisms and the construction of religion in Kyrgyzstan - McBrien, Julie (University of Pittsburgh Press, 2017)
"This book presents a nuanced ethnographic study of Islam and secularism in post-Soviet Central Asia, as seen from the small town of Bazaar-Korgon in southern Kyrgyzstan. Julie McBrien explores belief and non-belief, varying practices of Islam, discourses of extremism, and the role of the state, to elucidate the everyday experiences of Bazaar-Korgonians. She shows how Islam is explored, lived, and debated in both conventional and novel sites, and argues that religion is not always a matter of belief--sometimes it is essentially about belonging. McBrien details the complex process of evolving religion in a region that has experienced both Soviet atheism and post-Soviet secularism, each of which has profoundly formed the way Muslims interpret and live Islam"--